The Role of Four-Wheel Dialogical Patrol in Preventing Motorcycle Theft - Rahman Kurniawan, Arie (Indonesian Journal of Police Studies, 2024)
Motivated by threats to internal security in Cirebon City which is caused by high rate of motorcycle theft in the past three years. Based on the UU RI No. 2 year 2002, Police have principal task of maintaining internal security by performing prevention activities through patrols dialogic four-wheel Sabhara Unit. There are three issues posed in writing of this thesis, the general description of motorcycle theft, role of the patrol dialogic four-wheel in preventing motorcycle theft, and factors that affect role of the patrol dialogic four-wheels in preventing motorcycle theft. To analyze against those issues, method of field research with a qualitative approach are used. Conceptual framework in form of theories and concepts are used as a knife analysis by researcher in answering problem. The theories and concepts used by researcher are theory of routine activity, role theory, management theory, concept of the patrol, and concept of a criminal offense. As for result of this writing are general description of motorcycle theft in Polres Cirebon Kota occur due to three factors, motivated offenders, suitable victim, and absence of capable guardian. The role of Sabhara Unit in preventing motorcycle theft is due to poor management of the four-wheel dialogic patrol, and factors that affect are men, money, material, method, machine, and market. From the findings of the writing, it is expected to that patrol officers will cary out their duties professionally. Then it is suggested in adding more personnel and conduct vocational education and training on patrol.